2022
DOI: 10.3389/fnhum.2022.977776
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal resting-state connectivity predicts affective neurofeedback performance

Abstract: Neurofeedback has been suggested as a potential complementary therapy to different psychiatric disorders. Of interest for this approach is the prediction of individual performance and outcomes. In this study, we applied functional connectivity-based modeling using electroencephalography (EEG) and functional near-infrared spectroscopy (fNIRS) modalities to (i) investigate whether resting-state connectivity predicts performance during an affective neurofeedback task and (ii) evaluate the extent to which predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
0
2
0
Order By: Relevance
“…Functional connectivity and brain network definition have developed rapidly in NF research across neuroimaging techniques. For instance, some studies have found connectivity measures related to specific networks that are closely related to success in NF paradigms (Pereira, Sayal, et al, 2023;Trambaiolli et al, 2022).…”
Section: Future Directionsmentioning
confidence: 99%
“…Functional connectivity and brain network definition have developed rapidly in NF research across neuroimaging techniques. For instance, some studies have found connectivity measures related to specific networks that are closely related to success in NF paradigms (Pereira, Sayal, et al, 2023;Trambaiolli et al, 2022).…”
Section: Future Directionsmentioning
confidence: 99%
“…However, larger RCTs are needed to provide evidence for the specificity and clinical relevance of symptom improvements [80]. FNIRS may be particularly suitable for achieving this goal, and first studies have provided proof-of-concept of DLPFC fNIRS neurofeedback [87,88]. Finally, an uncontrolled proof-of-concept study has shown promising preliminary results in reducing symptoms in social anxiety disorder using fNIRS neurofeedback [87].…”
Section: Prefrontal Brain Functionmentioning
confidence: 99%